Efeitos do tele-exercício síncrono e assíncrono, na força muscular, desempenho funcional e no equilíbrio de pessoas idosas: ensaio clínico randomizado - Giuliani, Fernanda Nelli Gomes (2024)
Aging is a progressive and multifactorial process. Among the conditions prevalent in the elderly population, the following stand out: decreased muscle strength, increased risk of falls and functional impairment. Regular multicomponent physical exercise can promote hypertrophy, increase muscle strength, improve functional performance and balance. Technology appears as an ally in promoting a healthy lifestyle, encouraging the practice of physical exercises. Remote intervention, although widely investigated, still lacks consensus regarding its effectiveness, mainly due to the variability in intervention modes. The objective of the study was to evaluate muscle strength, functional performance and balance of older adults before and after performing tele-exercises in synchronous and asynchronous modalities. The hypothesis is that both modalities promote improvements in the evaluated variables, with greater adherence expected in the synchronous group due to socialization. This was a randomized, controlled, parallel-group clinical trial with blinded assessments and a quantitative approach. Isokinetic, handgrip, Short Physical Performance Battery, Timed Up and Go, and Unipedal Stand Test were used for evaluation. The intervention was carried out synchronously and asynchronously three times a week, lasting 50 minutes, for 12 weeks. Results: A total of 49 older adults participated in the study. The synchronous group had greater attendance compared to the asynchronous group. Men in the synchronous group showed improvements in muscle strength and balance compared to the asynchronous group. There was no difference in functional performance. It can be concluded that tele-exercise in synchronous mode has potential for applicability aiming at promoting health, improving muscle strength and physical activity levels, as well as preventing negative outcomes resulting from a sedentary lifestyle.